The Chemokine Receptors - Harrison, Jeffrey K.; Lukacs, Nicholas W. (The Receptors, 2007)
To date, there are over twenty different chemokine receptors, binding nearly fifty unique ligands that have been identified. In Chemokine Receptors, leading investigators attempt to distill the large body of literature ranging from basic molecular and cellular mechanism of chemokine receptors, to physiological and pathological roles of chemokines. Chemokines exhibit a tremendous functional diversity and participate in a wide variety of processes that include inflammation, innate and adaptive immunity, immune cell differentiation, angiogenesis, tumorigenesis, development, neurobiology and viral pathogenesis. Chemokine Receptors targets the pharmaceutical industry, provides an authoritative perspective on the future direction of this field, and insights into areas of active development of novel therapeutics.